2022
DOI: 10.1002/adma.202203417
|View full text |Cite
|
Sign up to set email alerts
|

“Tree‐Trunk” Design for Flexible Quasi‐Solid‐State Electrolytes with Hierarchical Ion‐Channels Enabling Ultralong‐Life Lithium‐Metal Batteries

Abstract: theoretical energy density, low reduction potential of metallic Li, and their inherent safety provided by the solid-state electrolyte (SSE), [1][2][3] As the core component, the development of SSE with superior lithium-ion conductivity and stability plays a critical role in the realization of such batteries. [4][5][6] Compared to oxide or sulfidebased inorganic SSEs which are brittle and difficult to process, organic SSEs, such as poly(ethylene oxide), received wide attention due to their advantages including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…However, a limited number of polymer types such as PTFE binder are suitable for this method [ 62 , 63 ]. Additionally, developing mechanically flexible electrolytes that can accommodate volume changes of sulfur could be another effective strategy to gain highly mechanically stable ASSLSBs [ 64 , 65 ].…”
Section: Challenges and Solutions For The Composite Sulfur Cathodementioning
confidence: 99%
“…However, a limited number of polymer types such as PTFE binder are suitable for this method [ 62 , 63 ]. Additionally, developing mechanically flexible electrolytes that can accommodate volume changes of sulfur could be another effective strategy to gain highly mechanically stable ASSLSBs [ 64 , 65 ].…”
Section: Challenges and Solutions For The Composite Sulfur Cathodementioning
confidence: 99%
“…[16] QSSE may be an effective strategy to improve both safety and electrochemical performance. [17] Hou et al [18] identified solvent-assisted jumping as the main route of lithium-ion transport in the MOF-688 material and explained the key role of solvents. Yang et al [19] used the molecule-anion coordination to promote the dissociation of lithium salts, increase the concentration of free lithium ions, and achieve the fixation of anions, which weakened the dynamic traction of lithium ions when moving, and greatly enhanced the transport dynamics of lithium ions.…”
Section: Introductionmentioning
confidence: 99%
“…Vertically heterostructured PEO-based solid electrolytes (HPSE) are hybrid multilayered solid ion conductors with homogeneous composition in each layer . At the side of the Li anode, nanofillers can be added to enhance the mechanical properties of PEO, such as SiO 2 , , Al 2 O 3 , , BN, , MOFs (metal–organic frameworks), and Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 . ,, At the cathode side, the flexibility and ionic conductivities of PEO-based SPEs can be increased by introducing plastic crystals, such as succinonitrile (SN), , which has attracted great attention as a typical solid plastic crystal. In 2004, Armand et al first introduced SN as a universal matrix for solid-state ionic conductors and found that the ionic conductivity of SN-lithium bis­(trifluoromethane)­sulfonimide (LiTFSI) could reach 3 mS cm –1 .…”
Section: Introductionmentioning
confidence: 99%